Law on Adoption - The Nationnal Assembly (2010)
This Law provides the principles and conditions for adoption; competence, order and procedures for settling adoptions; rights and obligations of adoptive parents, adopted children and natural parents; and responsibilities of agencies and organizations in adoption.